Promoting Sustainable Mobility: Impact of an Urban Biking Programme on University Students - Milena Adaros-Boye (MDPI AG, 2021)
The use of bicycles is an active and sustainable mode of transport par excellence. It is a way of increasing people’s physical activity time and should therefore be promoted in educational contexts. The aim of this research was to evaluate the effectiveness of an urban bicycle programme in a sample of 164 university students (n = 164), 88 women and 76 men, using a standardised instrument with pre and post measures after a theoretical–practical intervention. The sample was divided into an intervention group (n = 122) with 69 women and 53 men; and a control group (n = 42) with 19 women and 23 men. The instrument considered conceptual and attitudinal aspects. The results showed that participants in the intervention group obtained statistically significant improvements (p ≤ 0.05) in the measurement. No significant improvements were observed in the control group (p = 0.35), which means that the urban intervention programme is an effective method for increasing bicycling knowledge and attitudes in the university students who participated in the experience.